ChemInform Abstract: Palladium—Polypyrrole Nanoparticles‐Catalyzed Sonogashira Coupling. Issue 15 (25th March 2013) - Magdesieva, Tatiana V.; Nikitin, Oleg M.; Zolotukhina, Ekaterina V.; Zinovieva, Veronika A.; Vorotyntsev, Mikhail A.
Abstract Pd‐Nanoparticles encapsulated into polypyrrole globules are found to be an active catalyst for the Sonogashira coupling of iodo‐ and bromoarenes.